If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4x-7=65
We move all terms to the left:
-4x-7-(65)=0
We add all the numbers together, and all the variables
-4x-72=0
We move all terms containing x to the left, all other terms to the right
-4x=72
x=72/-4
x=-18
| 5x-10=47-4x-3 | | 4x-4=4x=6 | | 3x+12=12*x-12 | | x-7=-61+7x | | 3(x-1)=1+2 | | 7x-3=1+4x | | 6(y-3)+3(y+4)=21 | | -6x-2=4x-102 | | 56=-7(6y+4) | | 3-4(4x-5)=-5 | | 3-4(4x-5=-5 | | (a+3)*(a-1)-(a-3)*(a+2)=15 | | -w+218=6 | | -0.8k+7=-0.7k+1 | | 7y+3-5y=29 | | 16=f=18 | | 10y-5=3y+2 | | 2*(2x^2+x)=4*(6+x^2) | | 126=206-u | | -x+63=202 | | 57-x=291 | | 26=-2(8-3x) | | k4+ 5=8 | | 57=9w+3 | | -8=2(y-8) | | w/4+9=10 | | -54=9-7u | | 3x+15/4+x+27/6=11 | | 3x+15/4+(x+27/6)=11 | | 2u-1=15 | | (x-9/7)+(9/7)=(-x/3) | | 12x2-23x+5=0 |